T cell responses to 60/65 kDa heat shock protein derived peptides in Turkish patients with Behcet's disease - (:unkn) unknown (J RHEUMATOL PUBL CO, 2000)
Objective. Sequence homology and cross reactivity between microbial and human heal shuck proteins (HSP) led to the concept that HSP might be involved in the etiopathogenesis of Behcet's disease (BD). We investigated T cell responses to 8 synthetic peptides derived from the mycobacterial 65 kDa and homologous human 60 kDa HSP in patients with BD. Methods, T cell proliferative responses to synthetic peptides were studied in 49 patients with BD and 46 disease (DC) and 34 healthy controls (HC) with H-3-thymidine uptake test. Results, Positive T cell responses to one or more of the mycobacterial peptides were observed in 52% (12/23) of patients with BD compared with 17% (3/18) of DC (p = 0.02) and to homologous human peptides in 57% (13/23) of BD and 11% (2/18) of DC (p < 0.01). Responses to the mixtures of 4 mycobacterial peptides were also significantly higher in BD compared with controls (stimulation index in BD 4.7 +/- 3.5 vs DC 2.0 +/- 1.7, HC 16 +/- 0.4: BD vs DC and HC, p < 0.001). Similar elevated responses es to the mixture of 4 human peptides was also observed in patients with BD (BL) 3.4 +/- 2.3: DC 1.9 +/- 0.8; HC 1.4 +/- 0.6, BD vs DC, p < 0.01; BD vs HC, p < 0.001). Conclusion. These results suggest that cellular immunity against the 65 kDa mycobacterial and 60 kDa human HSP derived peptides is significantly increased in Turkish patients with RD compared to controls, as observed in the UK and Japan.
Keywords: Behcet's disease; heat shock proteins; cellular immunity; IMMUNOHISTOLOGY; MYCOBACTERIAL; RECOGNITION; INDUCTION; EPITOPE; HSP